Implementação da rastreabilidade na produção integrada de pêssego - Tibola, Casiane Salete (2008)
The related incidents with the contamination of foods had determined the necessity of guarantees of alimentary security, through the traceability, making possible the identification of risks and the adoption of efficient measures for the control. In this context, the aim of this work was the implementation and validation of an efficient and effective traceability system in the integrated production of peaches (IPP) for industry, assuring the quality and safety of fruits. The implementation of PIP and the traceability, in the production, was carried through mount visits, from the beginning of the vegetative cycle to the after-harvest. The parcels in the orchards were determined through a GPS data receiver (Global Positioning System), and the identification was made through registers in the field notebook. In the harvest, the boxes were identified with labels which contained producer, parcel, cultivar, date and time of the harvest. In act of receiving in the industry, lots had been formed, taking into account homogeneity, cultivar and amount of fruits. Each lot entered individually in the line of processing, establishing an interval between themselves. After definition of the lots, the information contained in labels of the boxes were captured through optic reader, conducting the information to the data base by specifying the number of boxes of each producer. In each lot, it was monitored quality of the peach in syrup, through physicochemical analyses, in agreement with the after-harvest notebook industry of the IPP. From the given informations, the products with the bar code EAN/UCC-128 were identified, with the following xiii information: peach/industry; category; weight; date of manufacturing and validity; time; variety; number of the lot; and the written traceability. Individually in the cans they printed the matters: validity/manufacturing date and lot/number. The storage, production and transportation conditions were measured in order to verify the conformity level to the IPP rules by the examination lists to adhesion and attendance auditing The causes of no-conformity and limitations to IPP adoption and traceability were studied. The production of monitored peach in syrup, of the extra and special categories increased gradually and in 2004/05 cycle it was of 1.600.000 cans. The registers stored in the monitoring make possible the maintenance of the description of each produced lot, specifying the provenance of all the components used in manufacturing of the peach in syrup. The collected informations in the productive chain were transcribed to the software that stores them and allows the access to the purchasers or consumers by typing the number of the lot printed in the can, through available page in Internet. The adoption of the IPP results in obtaining fruits with quality and generating records which make possible to control all of the adopted cultural